Governing complexity : analyzing and applying polycentricity - Thiel, Andreas; Blomquist, William A. (William Andrew), 1957-; Garrick, Dustin E. (Cambridge : Cambridge University Press, 2019)
There has been a rapid expansion of academic interest and publications on polycentricity. In the contemporary world, nearly all governance situations are polycentric, but people are not necessarily used to thinking this way. Governing Complexity provides an updated explanation of the concept of polycentric governance. The editors provide examples of it in contemporary settings involving complex natural resource systems, as well as a critical evaluation of the utility of the concept. With contributions from leading scholars in the field, this book makes the case that polycentric governance arrangements exist and it is possible for polycentric arrangements to perform well, persist for long periods, and adapt. Whether they actually function well, persist, or adapt depends on multiple factors that are reviewed and discussed, both theoretically and with examples from actual cases.
An introduction to polycentricity and governance / Mark Stephan, Graham Marshall, Michael McGinnis -- Seeing polycentrically : examining governance situations using a polycentricity lens / William A. Blomquist and Nadine Jenny Shirin Schroeder -- Foundational aspects of polycentric governance : overarching rules, social-problem characteristics and heterogeneity / Andreas Thiel and Christine Moser-Priewich -- Evolutionary institutional change and performance in polycentric governance / Andreas Thiel, Raúl Pacheco-Vega, Elizabeth Baldwin -- Cooperation in polycentric governance systems / Tom Koontz -- Conflict and conflict resolution in polycentric governance systems / Tanya Heikkila -- Competition in polycentric governance systems / Dustin E. Garrick, Sergio Villamayor-Tomas -- Assessing performance in polycentric governance system interactions / Tom Koontz, Tanya Heikkila, Dustin E. Garrick, and Sergio Villamayor-Tomas -- Polycentricity and citizenship in environmental governance / Graham Marshall and Anas Malik -- The Faustian bargain : power-sharing, constitutions, and the practice of polycentricity in governance / Vlad Tarko, Edella Schlager, Mark Lutter -- Practicing polycentric governance / Bryan Bruns.
Title from publisher's bibliographic system (viewed on 17 Sep 2019).
Keywords: Social structure; Pluralism; Complexity (Philosophy); Organization